Development of In Vitro Evaluation System for Assessing Drug Dissolution Considering Physiological Environment in Nasal Cavity - Daisuke Inoue; Ayari Yamashita; Hideto To (MDPI AG, 2022)
Estimating the dissolution behavior of a solid in the nasal mucus is challenging for solid dosage forms designed for the nasal application as the solid dissolves into nasal mucus and permeates through the mucosa. In the current study, the dissolution behavior of powders in the artificial nasal fluid was investigated using a 3D-printed chamber system to establish in vitro evaluation system for the dissolution of solid formulations that can simulate the intranasal environment in vivo. The dissolution rates of the five model drugs correlated with their solubility (r2 = 0.956, p < 0.01). The permeation rate of drugs across the Calu-3 cell layers after powder application depends on the membrane permeability of the drug. An analysis of membrane permeability considering the dissolution of powders showed the possibility of characterizing whether the drug in the powder was dissolution-limited or permeation-limited. This suggests that critical information can be obtained to understand which mechanism is more effective for the improvement of drug absorption from powders. This study indicates that the elucidation of drug dissolution behavior into nasal mucus is an important factor for the formulation of nasal powders and that the in vitro system developed could be a useful tool.